Hang 'em high [videorecording (DVD)] - Post, Ted, 1918-2013; Eastwood, Clint, 1930-; Stevens, Inger, 1934-1970; Begley, Ed, 1901-1970 (Metro Goldwyn Mayer ; Distributed by Twentieth Century Fox Home Entertainment, 2006)
Jed Cooper is mistaken for a criminal and is unjustly hung by the ruthless Captain Wilson and his nine-man gang, who leave him for dead. Cooper escapes the lynching and sets out on a deadly rampage of revenge against his persecutors.